Empowerment of Youth Cadres in HIV/AIDS Prevention Efforts at Youth Health Post of Nurul Anwar Boarding School, Komba, Sentani - Hasnia, Hasnia; Vitania, Wiwit; Pratami, Yustika Rahmawati; Lestari, Susi; Nasrianti, Nasrianti; Said, Fathia Fakhri Inayati (Universitas Malahayati Lampung, 2025)
ABSTRACT The many reproductive health problems of adolescents, then the provision of information, services and education on reproductive health of adolescents becomes very important. Adolescent problems that are closely related to reproductive health are often rooted in the lack of information and understanding and awareness to achieve reproductive health. Adolescent access to these service places is very low. To overcome health problems that occur in adolescents, comprehensive efforts are needed, namely by forming a youth health post. Youth cadres have an important role in providing information to the community, especially about adolescent health. The important role of peers is as a source of knowledge other than that obtained within the family. Peers are a form of a teenager's external environment. If adolescents have peers who have good behavior and knowledge about HIV/AIDS, it will contribute greatly to preventing adolescents from contracting HIV/AIDS, so it is necessary to provide assistance and information to youth cadres so that they can help disseminate the information provided. The method used is through an analytical approach, problem identification, intervention planning and implementation, namely empowering youth cadres in preventing HIV/AIDS by providing information and teaching cadres to conduct basic health checks, namely general condition checks. Providing education about HIV/AIDS, risk behavior for HIV/AIDS transmission (free sex, drugs and alcohol) found that youth cadres were very enthusiastic and interested in learning the guidance provided so that youth cadres would be more confident in carrying out their duties as youth cadres at the Youth Health Post. Keywords: Youth Cadres, Education, HIV/AIDS, HIV/AIDS transmission risk behavior and HIV/AIDS prevention.